PARTICIPATION IN ACTIVITIES – DETERMINANTS AND REFLECTION ON QUALITY OF LIFE AND SATISFACTION IN OLD AGE POPULATION IN BULGARIA - Tosheva, Ekaterina (Revista Inclusiones, 2020)
Social participation is a part of the concept of active ageing and it is among the important and effective factors for the elderly people’s welfare and good health. The aim of the present empirical study is to reveal the rate of participation of Bulgarians aged over 55 in various activities including social participation and to examine the effect of social participation on their life. The data used in the study are from the seventh wave of Survey of Health, Ageing and Retirement in Europe (SHARE), conducted in Bulgaria for the first time in 2017 and covers random sample of 2006 individual interviews. Relationships between socio-demographic and economic characteristics and activity participation on the one hand, and between activity participation and quality and satisfaction of life, self-perceived health and recall of words as measure of cognitive abilities on the other hand are studied. The majority of respondents (57%) reported that they had not participated in any of the studied activities. The proportion of respondents who participated in at least one individual activity was significantly higher than that of respondents who participated in collective activities. There were significant differences between the groups formed by gender, age, marital status, level of education, place of residence, financial status and health status. Participation in various activities, and especially in collective ones, had a significant beneficial effect on the measures of quality and life satisfaction, self-assessment of health and cognitive skills. These results support the idea in the concept of active ageing that it is important to provide opportunities for the elderly to participate in society according to their desires and abilities.